The Cosmic History of Black Hole Growth from Deep Multiwavelength Surveys - Ezequiel Treister; C. Megan Urry (Advances in Astronomy)
Significant progress has been made in the last few years on understanding how supermassive black holes form and grow. In this paper, we begin by reviewing the spectral signatures of active galactic nuclei (AGN) ranging from radio to hard X-ray wavelengths. We then describe the most commonly used methods to find these sources, including optical/UV, radio, infrared, and X-ray emission, and optical emission lines. We then describe the main observational properties of the obscured and unobscured AGN population. Finally, we summarize the cosmic history of black hole accretion, that is, when in the history of the universe supermassive black holes were getting most of their mass. We finish with a summary of open questions and a description of planned and future observatories that are going to help answer them.